2008
DOI: 10.1021/ie070996n
|View full text |Cite
|
Sign up to set email alerts
|

Design and Control of an Isopropyl Alcohol Dehydration Process via Extractive Distillation Using Dimethyl Sulfoxide as an Entrainer

Abstract: In this paper, design and control of an isopropyl alcohol (IPA) dehydration process via extractive distillation have been investigated. The heavy-boiling entrainer used to aid the separation is dimethyl sulfoxide (DMSO). The design flowsheet includes an extractive distillation column and an entrainer recovery column with the top product of the extractive distillation column to be IPA and the top product of the entrainer recovery column to be water. The bottom product of the entrainer recovery column is the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(105 citation statements)
references
References 39 publications
2
101
0
2
Order By: Relevance
“…The condenser heat duty is then neglected despite its impact on the process cost; and the regeneration column is not taken into account. Arifin and Chien (2008) used the total annual cost (TAC) including capital cost and operating cost as objective function. They showed that it exhibits a minimal value vs the total number of trays for the extractive process sequence columns.…”
Section: Objective Function (Of)mentioning
confidence: 99%
“…The condenser heat duty is then neglected despite its impact on the process cost; and the regeneration column is not taken into account. Arifin and Chien (2008) used the total annual cost (TAC) including capital cost and operating cost as objective function. They showed that it exhibits a minimal value vs the total number of trays for the extractive process sequence columns.…”
Section: Objective Function (Of)mentioning
confidence: 99%
“…The constant reflux ratio and constant entrainer feed rate operating policy, and another policy to allow these two operating variables to be varied, will be compared in order to further improve batch operation. Arifin and Chien (2008) have investigated the control of an isopropyl alcohol (IPA) dehydration process via extractive distillation. The heavy-boiling entrainer used to aid the separation is dimethyl sulfoxide.…”
Section: Fig 1 -Conventional Extractive Distillation Sequence (Ds)mentioning
confidence: 99%
“…In the stripping section, the αwater-AA is much lower than that in the extractive section (between 2 and 3). This phenomenon is different from other extractive distillation systems such as ethanol-water [33], acetone-methanol [25], isopropyl alcoholwater [32] and so on. The reason is that even there is not azeotrope formation between water and AA, the average relative volatility of water is close to unity (see Fig.…”
Section: Comparisons From Ternary Map and Relative Volatilitymentioning
confidence: 99%